Endoscope ear pick: An emerging but neglected medical device - Huang, Wendi; Li, Ying; Huang, Juan; Luo, Yong; Huang, Nanqu (Frontiers in Medicine, 2022)
Earwax (cerumen), a normal bodily secretion, can become a problem when it obstructs the ear canal. Due to the special position of the ear and the complex structure of the ear canal, it is not an easy task for us to remove earwax by ourselves or even with others’ help. using ear scoops or cotton swabs to dig out ear wax in daily life are like “a blind man walking on cliff”. Improper operation may damage the ear canal or even the eardrum, so we need a pair of visible "eyes", otoscopes, to help us see earwax intuitionistic. Traditional otoscopes only have the function of seeing, while now the endoscope ear pick will help us both see and remove earwax or other foreign bodies. In this review, we concluded the pros and cons of endoscope ear pick and look into their future role.